Evaluación de dexmedetomidina y dexametasona como analgésicos adyuvantes en el bloqueo de los nervios ciático y femoral con levobupivacaína para cirugía de rodilla en perros - Cervantes Zapata, María Alejandra (2023)
The study aimed to compare the efficacy and duration of postoperative analgesia using dexmedetomidine or dexamethasone as adjuvants to levobupivacaine for sciatic and femoral nerve blocks in dogs undergoing therapeutic knee surgery. Likewise, to evaluate the concordance between the Glasgow and Melbourne pain scales and between evaluators. Twenty-four dogs requiring knee surgery as part of their treatment were selected and randomly distributed into three treatments (control, dexmedetomidine, dexamethasone). The peri-neural block of the sciatic and femoral nerves was guided by a neurostimulator prior to the surgical procedure. Pain assessment was done before and every two hours during the 24 hours after the procedure, using the Melbourne and Glasgow scales by two independent and blind evaluators. The variation of heart rate (ΔHR) and respiratory rate (ΔFR) was evaluated. These variables were compared between treatments and moments by the Friedman test. The ΔFC, ΔFR and the Glasgow scale were similar between treatments (p>0.05). The Melbourne scale reported lower values in the dexmedetomidine group (p=0.0019) and less need for analgesic rescue (p=0.0338). It is concluded that dexmedetomidine has an adjuvant and prolonging effect on local anesthetic blockade, reduces pain intensity and the need for analgesic rescue, in addition, it was possible to determine that the variation between pain evaluators is minimal and that the Melbourne scale presents greater sensitivity to identify analgesic rescue requirement.